Ruptured renal angiomyolipoma treated by transcatheter arterial embolization report of two cases - Yamaguchi, Yuichiro (Hinyokika kiyo. Acta urologica Japonica, 2004)
We report two cases of spontaneous rupture of renal angiomyolipoma (AML). In the first case, a 22-year-old woman was admitted with lower abdominal pain. She was diagnosed with rupture of left renal AML. Transcatheter arterial embolization (TAE) was performed for three times to preserve renal function, and the size of AML decreased to 6.5 cm from 10 cm. In the second case (74-year-old woman), the chief complaint was lower abdominal pain. The clinical diagnosis of this patient was rupture of right renal AML. The size of this AML markedly reduced due to TAE. TAE is an effective therapy for rupture of renal AML